Impact of Diabetes Mellitus Type-II on Patient’s Quality of Life in Sindh, Pakistan (Medical Forum Monthly, 2022)
Objective: To evaluate the impact of type II diabetes mellitus on patient’s quality of life visiting tertiary care hospital in Hyderabad, Sindh, Pakistan.Study Design: Descriptive Cross-sectional study.Place and Duration of Study: This study was conducted at the Liaquat University Hospital, Hyderabad, from August 2019 to January 2020.Materials and Methods: A sample size of 168 was obtained and participants were selected by using Non-probability convenient sampling technique and all Patients between the ages 25 years and 40 years, known cases of type2 diabetes mellitus, belongs to either sex, gave consent of participation, visited the outpatient department of diabetes/ medical clinics at Liaquat University Hospital during the study duration were included. Patient’s information related to etiological factors of disease and its symptoms was collected using written questionnaire. Quality of life in type-II diabetics was evaluated through a World Health Organization D-39 Questionnaire. Data was analyzed using SPSS version. 23.Results: Total 168 type -II diabetic patients were included in the study. Findings of the study were depicting the mean QoL score of type- II diabetics as 52.1. Score of various domains indicating the QoL in type-II diabetics was classified as 55% in physical, 47% in psychological, 55% in social and 50% in environmental domain of QoL. Overall domain wise scoring revealed an average QoL.Conclusion: Type-II diabetes significantly affects the quality of life in physical domain along with psychological domain. QoL is badly affected in type-2 diabetic patients. Diabetes has an adverse influence on all the aspects of life in affected patient.